Effects of sisal nanofiber addition to epoxy resin-based sealer on its antibacterial power against Enterococcus faecalis - Heny Retno Mayangsari; Tunjung Nugraheni; Ema Mulyawati (Majalah Kedokteran Gigi Indonesia, 2021)
Sealer is one of root canal filler materials which has been developed and has an antibacterial agent to keep root canal sterile during and after an obturation process. This study aimed to find out the effect of sisal nanofiber addition to resin epoxy-based sealer on the antibacterial power against Enterococccus faecalis (E. faecalis) which is known as adaptive and potent bacteria which can be both aerobic and anaerobic. Sisal fibers were processed through many stages to make it nano sized (scouring, bleaching, neutralization, ultrasonification, and freeze-drying). Once nano-sized sisal fibers had been obtained, they were then mixed with sealer powder (AH26) in different concentrations: powder 0%, 0.25%, 0.5%, 0.75% and 1%. These concentrations were chosen based on preliminary research for reasonable contact angle measurement of sisal-sealer mixture. Antibacterial effect was examined using the diffusion method, each concentration was tested in 5 petri dishes which were planted with 1.5 X 108 CFU/ml E.faecalis bacteria. Each dish consisted of 5 holes (6 mm in diameter), each hole represented each concentration of nano sisal and sealer which were mixed until homogenous for 3 minutes before added to each hole. The dishes were then incubated for 48 hours at 37 °C. Inhibitory zones were measured, and analyzed using one-way ANOVA. The one-way ANOVA result showed that p=0.502 (p>0.05), meaning that the sisal nanofiber addition to epoxy resin-based sealer had no effect on E.faecalis inhibition. Thus, there was no effect of sisal nanofiber addition to epoxy resin-based sealer on E. faecalis.